Prevalence and Molecular Characterization of Vibrio Parahaemolyticus Isolated from Cultured Tiger Prawns(Penaeus Monodon) from Malacca - Tuan Chilek, Tuan Zainazor (2006)
Food industries play an important role and contribute to economic activities in many countries worldwide. However, the frequencies of outbreak of food borne cases reported around the world related to this industry posed a significant public health issue. All countries including Malaysia have already developed their own food laws and food regulations to protect public health and to prevent food borne outbreaks. However, despite the strict controlled at every stages of food production, from farm to table, food borne outbreaks still occur. Tiger Prawn (Penaeus monodon) is synonymous with Malaysian farming industries. Vibrio parahaemolyticus is one of the major seafood-borne gastroenteritis-causing bacteria, frequently associated with consumption of improperly cooked seafood. Cultured tiger prawn farm at LKIM Merlimau, Malacca was identified for sampling in this study. The duration of sampling followed the whole cycle of tiger prawn cultivation (until harvesting stage) involving two cycles (from 29 September 2003 to 29 April 2004). A total of sixty samples of cultured tiger prawn (25g/sample) and pond’s water (25ml/sample) from both cycles were obtained. In our study, we found that most samples acquired were positive for V. parahaemolyticus (81.7%) when examined with specific-PCR (toxR). The presence of virulence gene, the tdh and/or trh genes have been considered the major virulence factor of the bacterium. In our study, none tdh gene was detected in all isolates. However, trh gene was detected in twenty-three isolates (38.3%) for both prawn and water samples. Temperature, pH and salinity play as an important factors in every stage of culturing tiger prawns. The optimum condition for those factors (temperature; 37oC, pH; 7.8-8.6, salinity; 3%) were promoted the growth of V. parahaemolyticus. RAPD-PCR was used to generate polymorphic genomic fingerprints to determine of genetic relatedness among V. parahaemolyticus isolates. Two primers (OPAR3; 5’-CTTGAGTGGA-3’and OPAR8; 5’-GAGATGACGA-3’), out of the ten primers showed the best results and were selected for further study. Primer OPAR3 and OPAR8 produced 1 to 8 bands and 1 to 9 bands, respectively with amplified products ranging from 0.25 to 10.0 kilo base pairs. Seven groups of antibiotics namely, the Aminoglycosides, β-lactams, Cephalosporins, Glycopeptides, Macrolides, Quinolones, Tetracyclines and others were tested against all V. parahaemolyticus isolates. They were highly resistant to ampicillin (100%), penicillin (100%), cefuroxim (100%), teicoplanin (100%), erythromycin (98%), rifampicin (98%), trimethoprim (98%) and streptomycin (96%), but sensitive to quinolones and tetracyclines groups of antibiotic. The antibiotic resistance profile patterns can be classified into four groups. In this study, MAR index range was between 0.40 – 0.60. Tiger prawn is a potential source of V. parahaemolyticus.